Penyuluhan Strategi Transformasi Desa Berkembang Menjadi Desa Maju dan Mandiri Berbasis IDM - Tajuddin, Tajuddin; La Ode, Suriadi; Novi Theresia, Kiak; Ernawati; Nur Azisah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This activity aimed to enhance village chiefs' and officials' understanding of the Village Development Index (Indeks Desa Membangun/IDM). In the short term, it focused on improving the comprehension of IDM concepts and applications. In the long term, it seeks to elevate village statusfrom developing to advanced and ultimately self-sufficient, thus contributing to sustainable regional development. Methodology: The counseling session was conducted in collaboration with Universitas Halu Oleo and Universitas Nusa Cendana. The participants included village representatives from Southeast Sulawesi and East Nusa Tenggara. The approach involved lectures to introduce IDM, discussions to explore participant insights, and simulations of hands-on practices. A pre-test was used to assess baseline knowledge. Results: The session led to a significant increase in participants’ understanding of IDM, especially regarding its three main dimensions: social, economic, and environmental indicators. Village heads and officials expressed readiness to apply the IDM data to evaluate village status and inform development planning. Conclusions: Post-test outcomes confirmed that participants grasped the importance of accurate IDM data input and could access indicator results through the website of the Ministry of Village Development. However, practical training on completing IDM questionnaires, especially for low-scoring indicators, is lacking. Future sessions should prioritize technical workshops for better implementation. Limitations: This activity did not include detailed guidance on completing the IDM questionnaires, limiting the practical application of knowledge. Conclusion: This initiative supports informed village planning and fosters collaboration between village and sub-district leaders, ultimately promoting data-driven rural development strategies based on IDM indicators.